Electronic rumors about the ‘corona pandemic’in algeria and its psychological effects on the public " Reading in the mechanisms of confrontation and confrontation" - Benriala , sara; Serai , souad (Social Empowerment Journal, 2020)
The rumors differ from other methods intargeting the community ,especialy in light of the conditions that humaniyu lives today due to the spread and spread of the corona epidemic, which made us approach this social phenomenon to identify its most important causes and motives for its spread and aggravation through social networking sites and the position of the Algerian state regarding these practices, and the most important mechanisms taken by the Algerian authorities regarding this type of malicious acts .where the most important results of the news were reached,whichare that false news is dangerous and can affect public order and the security and stability of society ,not to mention its prolonged and prejudice to the symbols of the state and its sensitive sectors .the Algerian state mcked it for curbing it and activating the most important new sanctions the authority over those involved in it, through the position of the Algerian legislator and the articles and provisions that have been developed in the Algerian penal code.